34. CHARACTERISTICS OF IRON LOAD STATUS IN THALASSEMIA PATIENTS RECEIVING IRON TREATMENT AT SAINT PAUL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Describe iron overload in thalassemia patients treated with iron chelation at Saint Paul General Hospital.Subjects: Include 46 thalassemia pediatric patients diagnosed and treated for iron overload at Saint Paul General Hospital from March 2023 to December 2023.Research methods: Prospective study, describing a series of cases.Results: The average age of the patients was 8.3 ± 3.56 years old, the 5-10 year old group had the highest rate (56.5%). The male ratio is 41.3%, female is 58.7%. The patient's serum ferritin concentration was high, with an average of 1818.99 ± 988.38 ng/ml. The group with moderate and severe ferritin accounts for 82.6%. 100% of patients have liver iron infection of all levels (mild to severe); the average liver iron concentration concentration was 11.06 ± 3.17 mg/g dry liver. There was a positive correlation with r = 0.627 between serum ferritin concentration and liver iron concentration. Severe liver iron infection in the serum ferritin ≥ 2500 ng/ml group was 21.875 times higher than the serum ferritin < 2500 ng/ml group, a significant difference with p < 0.05, OR = 21.875 and 95%CI = 3.147-152.048.Conclusion: Iron overload is a consequence of blood transfusion, accumulating in organs causing serious complications. Measuring serum ferritin levels and magnetic resonance imaging measuring liver liver iron concentration index help evaluate and monitor the body's level of iron overload.
Keywords: Thalassemia; iron overload; liver iron concentration